Tradução e adaptação cultural dos bancos de itens dos domínios Dificuldades Emocionais e Aspectos Sociais do Pediatric Patient-Reported Outcomes Measurement Information System - PROMIS Pediatric® (Versão 1.0) para língua portuguesa - Pinto, Márcia Neyza Ferreira de Castro (2014)
The Pediatric Patient-Reported Outcomes Measurement Information System (PROMIS Pediatric®) was developed by modern theories of statistical measures in order to assess more accurately the quality of life related to health of children and adolescents with chronic diseases. The aim of this study was to translate and culturally adapt the banks of items of domains Emotional Distress and Social Aspects of PROMIS Pediatric® from American English into Portuguese. The study was conducted according to the methodology Functional Assessment of Chronic Illness Therapy (FACIT) recommended by the developers of the PROMIS Pediatric®. The pre-test was conducted through cognitive interview with 10 participants between 8-17 years. In general, the items were well understood, only item 15 in Bank Anxiety required adjustments in the pre-test to achieve equivalence of meaning with the original version. In conclusion, translation from the banks of items Emotional Distress and Social Aspects into Portuguese version are semantically and conceptually equivalent to the original.